Relación de la motivación laboral con el desempeño laboral de los colaboradores del área de administración en una institución del estado, sede Callao – 2021 - Velásquez Mendoza, Valeria Sabrina (2022)
Nowadays, the employees of many companies and institutions do not feel motivated and this is observed in their work performance. Therefore, the following research studied the relationship of motivation with work performance in employees in the administration area of a state institution. The research presents a quantitative approach, applied non-experimental of a cross-sectional nature, with a correlational study method, since it seeks the relationship of two variables and was applied to 52 employees from the administration area. According to the results, it was evidenced that there is a significant relationship between motivation and job performance among employees of the state institution. It was observed that the level of motivation affects performance. Through the questionnaire made to the collaborators of the administrative area of the institution, it was possible to gather important information for the conclusions and recommendations. In addition, the study shows that intrinsic motivation is positively related to the responsibility of employees and with performance evaluation, likewise, extrinsic motivation is positively related to productivity.